Molecular determinants for the strictly compartmentalized expression of kainate receptors in CA3 pyramidal cells - Sabine Fièvre (Nature Portfolio, 2016)
Kainate receptors are selectively found at CA3-mossy fibre synapses, although the mechanisms regulating this compartmentalisation have yet to be determined. Here, the authors find KAR segregation is dependent on the amount of GluK2a protein and an interaction between the GluK2 C-terminal domain and N-cadherin.